PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP PRESTASI BELAJAR ILMU PENGETAHUAN ALAM SISWA KELAS V B MI Ya BAKII KALISABUK 02 - Laelatul Fajriyah; Wida Nurul Azizah (EL ROBIH: Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
The purpose of this research is to determine the results of learning achievement in Natural Sciences class V MI Ya BAKII Kalisabuk 02 and to determine whether or not there is an influence of teacher pedagogical competence on learning achievement in Natural Sciences class V B. This research uses 2 classes as research, namely class V A as control class and class V B as the experimental class with a research sample of 66 subjects. The approach used in this research is quantitative, with an experimental method with Pre-Experimental Design research type. Data collection was carried out using questionnaires and documentation of the results of daily repeat tests with Natural Sciences. For research analysis using the t-test. Based on the results of the research analysis, it can be concluded that: 1) There is an increase in the learning achievement of Natural Sciences students in class V B with an average score of 82, higher than the control class which got an average of 66. 2) Learning achievement with sig. (2-tailed) for the experimental class is 0.000 and the control class is 0.000, which means it is smaller than the limit used, namely 5% (sig < 0.05). in tcount it is obtained 7.019 > ttable (1.999). So Ho is rejected and Ha is accepted, meaning that there is an influence of teacher pedagogical competence on learning achievement in Natural Sciences.